Evaluation of the growth potential of local chickens in Malawi - Gondwe, T.N.P.; Wollny, C.B.A. (2005)
The growth potential of local chickens in Malawi was evaluated by comparing their growth performance under cage-fed and free-range management conditions. Chicks (n = 106) were collected from 39 farmers in 19 villages and individually raised in cages from an average age of 9 weeks to 20 weeks. Onfarm made growers mash (17 % CP) was fed and birds were treated against common diseases and parasites. Hatch mates (n = 141) of cage-raised chicks remained on farmer household flocks and were raised by their dam hens under scavenging conditions. These birds were raised in two batches between October and December 2002, and between January and March 2003, which were corresponding with hot-dry and warm-wet seasons, respectively. Sex of chickens, village, management and management x batch interaction significantly (p<0.05) influenced growth traits. The values for birds under cage-managed conditions were significantly (p<0.05) 27, 39, 42, 25 and 41% higher than for birds under scavenging conditions, for weight at 20 weeks, overall daily weight gains, specific growth rate and growth efficiency, respectively. Phenotypic variance for daily weight gains and specific growth rates were 17 and 21%, respectively lower for cage-fed than for free range birds. Correlation coefficients of growth traits measured between cage-fed and scavenging conditions were low (r = 0.21-0.53, p<0.05), indicating possible genotype by environment interaction. Gross margin over feed costs was MK26.00 per bird (SD, MK27.00). This was 35 % rate of return on feed costs (SD, 38 %) or 24 % rate of return on initial bird value plus feed cost (SD, =26). It is concluded that growth potential of local chickens is only partially exploited under scavenging conditions primarily due to feed constraints.